VOCABULARY ENHANCEMENT OF FEMALE ESL LEARNERS THROUGH SHORT STORIES: A RURAL/ URBAN PERSPECTIVE - Ahmed, Naseer (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Teaching English has progressed rapidly with the changing requirements of society. Current study has not only the purpose of testing vocabulary enhancement by short stories but also monitors its effects on rural and urban population at secondary level. Present study utilizes Pre-test, post-test experimental design. Before the commencement of study, 50 students took their pre-test from rural site and 50 students took their pre-test from urban site. Only those 20, 20 students were selected from both sites whose accumulative score was almost the same. After this, five short stories were taught to both groups for five weeks with the same methodology. After the completion of coaching, a post-test was conducted. Marks of pre-test and post-test of both rural and urban groups were compared to see difference in learning. Data was analyzed statistically by using SPSS 20 for windows. Analysis of data proved that urban group had statistically significant improvement as compared to rural group.